Dietary Glycemic Load, Glycemic Index, and Carbohydrate Intake on the Risk of Lung Cancer among Men and Women in Shanghai. (19th May 2018) - Sun, Jiang-Wei; Zheng, Wei; Li, Hong-Lan; Gao, Jing; Yang, Gong; Gao, Yu-Tang; Rothman, Nat; Lan, Qing; Shu, Xiao-Ou; Xiang, Yong-Bing
ABSTRACT: To investigate the potential influence of dietary glycemic index, glycemic load, or carbohydrate intake and lung cancer risk in Shanghai. We prospectively investigated the associations among 130, 858 participants in the Shanghai Women's and Men's Health Studies. Diet was assessed using validated food-frequency questionnaires. Lung cancer cases were ascertained through annual record linkage and every 2–3 years in-home visits. Cox proportional hazard regression model was used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). After excluding the first 2 years of observation, 1312 participants (including 649 women and 663 men) developed lung cancer during an average follow-up of 14.8 (SD: 2.0) years for SWHS and 9.3 (SD: 1.6) years for SMHS. In multivariable analysis, no statistically significant associations were observed between glycemic index, glycemic load, and carbohydrate intake and lung cancer risk for either men or women. Similar results were observed among never smokers, and participants without history of lung disease, diabetes, or hypertension. Stratification by body mass index or menopause status also did not alter the findings. Our studies, conducted in populations who habitually have high-carbohydrate diets, provide no evidence that dietary glycemic index, glycemic load, or carbohydrate intake is associated with lung cancer risk.